The effect of exercise intervention on balance and executive function in children with autism spectrum disorder: a meta-analysis - Haixia Li; Ruiyun Zhang (BMC Sports Science, Medicine and Rehabilitation)
Abstract Objective This study primarily evaluated the the effects of exercise intervention on balance and executive function in children with autism spectrum disorder (ASD). Methods Search for eligible studies through four databases, and then proceed with screening. The inclusion criteria are as follows: (1) Children with ASD; (2) Age 3–18 years; (3) Randomised Controlled Trial; (4) The intervention group received exercise training; (5) Conducted pre- and post-test, which include balance and executive function. Use the Cochrane bias risk assessment tool to evaluate the quality of the selected study. Select Standardized Mean Difference (SMD) as the appropriate effect scale index. Results Twelve of the selected articles involved 288 males and 108 females. The findings demonstrated that the exercise group (EG) benefited more from the improved balance than its control group (CG) counterpart [SMD = 0.86 (0.56, 1.16), p < 0.05, I2 = 37%]. Furthermore, subgroup analysis revealed that exercise interventions lasting over eight weeks significantly enhanced balance [SMD = 1.19 (0.79, 1.58), p < 0.05, I2 = 17%]. However, exercise interventions lasting less than or equal to 8 weeks did not have a significant impact on balance [SMD = 0.41 (− 0.06, 0.87), p = 0.09, I2 = 0%]. Conclusion Exercise interventions can better improve the balance and behavioural inhibition of children with ASD compared to CG. Nevertheless, physical training prescribed for more than eight weeks led to a more significant improvement in balance than interventions performed for shorter periods.